ANTARA MORAL EKONOMI DAN EKONOMI RASIONAL PADA POLA PROGRAM DENFARM S.R.I (Studi pada P3A Padibu Kecamatan Ulakan Tapakis dan P3A Banda Iduik Kecamatan Nan Sabaris) - Panji Asrywan; Damsar Damsar; Bob Alfiandi (Universitas Andalas, 2019)
This study aims to see the syncretism between the moral and rational economics of farmers on the Denfarm program pattern S.R.I in P3A Padibu and P3A Banda Iduik Ulakan Tapakis and Nan Sabaris Subdistricts. They also understand the relation of economic and moral rational syncretism of farmers to the Denfarm Pattern of S.R.I. The Denfarm program of S.R.I pattern is carried out by the government so that farmers can increase rice production. This activity was carried out on P3A Padibu and P3A Banda Iduik Ulakan Tapkis Subdistrict and Nan Sabaris Sub-District, but the results obtained were very different. There is a sociological problem affecting the Denfarm production pattern of S.R.I. The data analysis used is qualitative hermeneutical analysis using moral economic theory James Scoot and Rational Farmer Samuel Popkin. The result of the research shows that the low production of Denfarm pattern of S.R.I P3A Padibu is caused by the chairman who commits lying and stealing in order to reach the personal interest. Besides, the chairman has no sense of responsibility towards Denfarm activity which gives impact to the appearance of the lazy nature of other participants. Perta also has another more productive land so that participants ignore the results obtained from the land of the Denfarm program. The high production of Denfarm P3A Banda Iduik occurs because it has a rational thought but nature is formed because it wants to depends the good name of P3A group, therefore, they are afraid to fail in this activity